A polyurethane-based nanofiber membrane coaxially coated with a MOF layer and its preparation method and application

By using a polyurethane-based nanofiber membrane with coaxially coated MOF layer on the lithium-ion battery separator, the problem of existing membranes being easily melted and contracted at high temperatures is solved, and the high thermal stability and high electrolyte wetting of the membrane are achieved. , improves battery safety and performance.

CN118920024BActive Publication Date: 2025-02-25VICKSON SOLID CORE (DALIAN) TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411398830.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are prone to melt and shrink at high temperatures, resulting in battery short-circuit and combustion explosion problems. At the same time, their low porosity and low wettability affect the battery's resistance, energy density and magnification capabilities.

Method used

Polyurethane-based nanofiber membranes coaxially coated with MOF layer were prepared by electrospinning process, and the metal chelated polyaniline layer and MOF shell were modified in situ on its surface to form a porous structure to improve the separator Thermal stability and electrolyte wetting properties.

Benefits of technology

It significantly improves the heat resistance of the separator, the wetting properties of the electrolyte and the electrochemical properties, reduces the overpotential of the battery, and improves the safety and performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118920024B_ABST
    Figure CN118920024B_ABST
Patent Text Reader

Abstract

The present application discloses a polyurethane-based nanofiber membrane coaxially coated with a MOF layer, and a preparation method and application thereof. From the inside to the outside, it includes polyurethane nanofibers as a core layer, a metal chelated polyaniline layer as an intermediate layer, and MOF particles as a shell layer. Avoiding the use of polyolefin porous membranes, using a composite diaphragm formed by a combination of polyurethane and MOF materials with high thermal stability can fully guarantee the thermal shrinkage performance of the diaphragm. At the same time, the presence of the metal chelated polyaniline layer also ensures the close combination of the MOF layer and the polyaniline layer, avoiding the risk of the MOF layer falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a polyurethane-based nanofiber membrane coaxially coated with a MOF layer, a preparation method and application thereof, and belongs to the field of battery materials. Background Art

[0002] In recent years, due to the increasing consumption of fossil energy, there is an urgent need for clean energy to replace fossil energy. At the same time, clean, stable and efficient energy storage systems have also attracted widespread attention. Lithium-ion batteries (LIBs) with high energy density and stable cycle performance have rapidly dominated the energy storage system market for portable electronic devices such as smartphones, laptops and cameras. However, improper use of lithium batteries in life can easily cause safety problems such as combustion and explosion. As an important component of lithium-ion batteries, diaphragms have a significant impact on the capacity and performance of batteries. Using diaphragms to optimize battery performance, extend battery life, and solve battery safety issues is an effective method.

[0003] At present, the lithium-ion battery separators on the market are mostly focused on polyolefin separators such as polyethylene (PE) and polypropylene (PP). These polyolefin microporous membranes have good chemical stability and high mechanical strength. However, the low porosity and poor wettability of polyolefin membranes with polar liquid electrolytes seriously affect the battery resistance, energy density and rate capability of LIB. Polyolefin materials will melt and shrink at high temperatures, causing battery short circuits. A large amount of heat is released in a short period of time, causing the lithium-ion battery to burn or even explode. The ideal separator should have low interfacial resistance, high electrolyte wettability and uniform pore distribution to meet the requirements of normal operation of the battery in different applications. The separator needs to have the characteristics of high thermal stability, high mechanical strength and high wettability to meet these requirements. Therefore, it is very important to prepare separators by adjusting the raw material ratio and copolymerization of different polymers for the development of lithium-ion batteries. It is very important to develop separators with high thermal stability, high mechanical strength and high wettability to replace traditional commercial separators to further improve the performance and safety of lithium-ion batteries.

[0004] The electrospinning process has received widespread attention in the past two decades. Electrospinning technology can be used to continuously produce micron-sized nanofiber membranes. Nanofiber membranes have large specific surface area, high porosity, small pore size, and strong adsorption capacity, which can improve the wettability and thermal stability of the membrane. With the development and commercial production of large-scale electrospinning equipment, mass production of nanofibers has also become possible. Summary of the invention

[0005] In view of the deficiencies in the prior art, one of the objectives of the present invention is to provide a nanofiber membrane having good high temperature resistance, high wettability, thin thickness and low electrical resistance.

[0006] The second object of the present invention is to provide a method for preparing a polyurethane-based nanofiber membrane coaxially coated with a MOF layer. The preparation method is easy to control and can produce a high-quality diaphragm material that reduces battery quality risks and effectively improves battery safety.

[0007] The third object of the present invention is to provide application of the nanofiber membrane in lithium-ion batteries.

[0008] According to one aspect of the present application, a polyurethane-based nanofiber membrane coaxially coated with a MOF layer is provided, which includes, from the inside to the outside, polyurethane nanofibers as a core layer, a metal chelate polyaniline layer as an intermediate layer (for inducing the MOF layer to grow uniformly on the surface of the nanofibers), and MOF particles as a shell layer.

[0009] The metal chelated polyaniline layer is modified on the surface of the polyurethane nanofiber core layer;

[0010] The MOF particles and the metal chelated polyaniline layer are tightly combined;

[0011] The polyurethane nanofibers as the core layer have a porous structure.

[0012] The nanofiber membrane of the present application is provided with an electrospun polyurethane nanofiber core layer and a MOF shell layer modified in situ on the surface of the above-mentioned nanofiber core layer. Polyurethane material has excellent thermal stability, and using this material as a matrix can significantly improve the heat resistance of the diaphragm. In addition, the carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, so that the diaphragm has an extremely high liquid absorption rate, thereby enhancing the ionic conductivity of the diaphragm. The nanofiber core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the wettability and liquid retention rate of the electrolyte. The MOF shell layer also has high thermal dimensional stability, and the uniform pore size of MOF has the ability to regulate lithium ion transmission and induce uniform lithium deposition, thereby inhibiting dendrite growth, reducing the overpotential during the charge and discharge cycle, and improving the electrochemical performance of the battery. At the same time, there is a metal chelated polyaniline layer between the two layers, which is used to induce the MOF layer to grow uniformly on the surface of the nanofiber to form a polyurethane-based nanofiber membrane coaxially coated with the MOF layer.

[0013] The diameter of the polyurethane nanofiber is 200-600 nm;

[0014] The size of the MOF particles is 20-200 nm.

[0015] The polyurethane-based nanofiber membrane has a thickness of 10 to 100 μm;

[0016] Optionally, the polyurethane-based nanofiber membrane has a thickness of 15 to 45 µm.

[0017] The MOF is selected from at least one of ZIF-7, ZIF-8, ZIF-67, ZIF-7-NH2, UIO-66-NH2, and HKUST-1.

[0018] According to another aspect of the present application, a method for preparing the above-mentioned polyurethane-based nanofiber membrane coaxially coated with a MOF layer is provided, comprising the following steps:

[0019] 1) Polyurethane nanofibers were obtained by electrospinning and polyurethane nanofiber membranes were obtained by hot pressing;

[0020] Specifically, polyurethane is dissolved in an organic solvent to prepare a spinning solution. The spinning solution is added to a syringe and electrospun under the conditions of a voltage of 15-30 kV, an extrusion speed of 1.5-3 ml / h, and a receiving distance of 8-25 cm. The solution is collected and hot-pressed at 80-120° C. and 5-15 MPa for 3-15 minutes to obtain a polyurethane nanofiber membrane.

[0021] The organic solvent includes one or more of dimethylacetamide DMAC, N,N-dimethylformamide DMF, and dimethyl sulfoxide DMSO, and the solid content of the spinning solution is 5-30%.

[0022] 2) adding methanol to the polyurethane nanofiber membrane obtained in 1) to pre-wet the pores, then placing it in a solution containing aniline hydrochloride and ammonium persulfate for treatment, washing with hydrochloric acid and water in turn to remove residual precipitates, then placing it in ammonia water for neutralization, then placing it in a zinc nitrate solution for chelation, and drying to obtain a polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer;

[0023] In the solution containing aniline hydrochloride and ammonium persulfate, the concentration of aniline hydrochloride is 0.1-0.5 mol / L, and the concentration of ammonium persulfate is 0.1-0.8 mol / L;

[0024] Optionally, the concentration of aniline hydrochloride is any value among 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, or a range value between any two of them.

[0025] Optionally, the concentration of ammonium persulfate is any value among 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, or a range value between any two of them.

[0026] The treatment temperature is 0-10°C;

[0027] Optionally, the treatment temperature is any value of 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, or a range between any two of them.

[0028] The treatment time is 1 to 8 hours;

[0029] Optionally, any value among 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, or a range value between any two of them.

[0030] The concentration of the zinc nitrate is 0.1-0.6 mol / L;

[0031] Optionally, the concentration of zinc nitrate is any value among 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, or a range value between any two of them.

[0032] The chelating temperature is 60-90°C;

[0033] Optionally, the chelating temperature is any value of 60°C, 70°C, 80°C, 90°C, or any range therebetween.

[0034] The chelating time is 4 to 8 hours.

[0035] Optionally, the chelating time is any value among 4h, 5h, 6h, 7h, 8h, or a range between any two of them.

[0036] The chelation is chelation of metal zinc ions.

[0037] The hydrochloric acid concentration is 0.1~1 mol / L;

[0038] Optionally, the concentration of hydrochloric acid is any value among 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, or a range between any two of them.

[0039] The concentration of the ammonia water is 0.05-0.3 mol / L.

[0040] Optionally, the concentration of the aqueous ammonia is any value among 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, or a range value between any two of them.

[0041] The drying temperature is 55-80°C;

[0042] Optionally, the drying temperature is any value of 55°C, 60°C, 70°C, 80°C, or any range between two of them.

[0043] The drying time is 8 to 24 hours.

[0044] Optionally, the drying time is any value among 8h, 16h, 24h, or a range between any two of them.

[0045] 3) The polyurethane nanofiber membrane with the surface modified metal chelated polyaniline layer obtained in 2) is vertically suspended in an organic solution containing a MOF precursor, reacted, rinsed and soaked with methanol, and dried to obtain the polyurethane-based nanofiber membrane coaxially coated with the MOF layer.

[0046] The organic solution is selected from at least one of DMAC, DMF and DMSO.

[0047] The drying temperature is 55-80°C;

[0048] Optionally, the drying temperature is any value of 55° C., 60° C., 70° C., 80° C., or a range between any two of them.

[0049] The drying time is 8 to 24 hours.

[0050] Optionally, the drying time is any value among 8h, 16h, 24h, or a range value between any two of them.

[0051] In the organic solution containing the MOF precursor, the selection and content of the MOF precursor are adjusted according to the synthesis conditions of the different MOFs selected.

[0052] The specific conditions of the reaction are adjusted according to the synthesis conditions of the different MOFs selected.

[0053] According to another aspect of the present application, there is provided an application of the above-mentioned polyurethane-based nanofiber membrane coaxially coated with a MOF layer for use in lithium-ion batteries.

[0054] The beneficial effects of this application include:

[0055] 1) This application avoids the use of polyolefin porous membranes and uses a composite diaphragm formed by a combination of polyurethane with high thermal stability and MOF materials, which can fully guarantee the thermal shrinkage performance of the diaphragm. At the same time, the presence of the metal chelated polyaniline layer also ensures the close bonding between the MOF layer and the polyaniline layer, avoiding the risk of the MOF layer falling off.

[0056] 2) An innovative technical route for setting up coaxial MOF coating layers, including an electrospun polyurethane nanofiber core layer and a MOF shell layer modified in situ on the surface of the nanofiber. The electrospun polyurethane nanofiber core layer and the MOF shell layer can synergistically enhance the heat resistance of the diaphragm and significantly improve the safety performance of the battery. Combining electrospun nanofiber membranes with inorganic nanoparticles to prepare composite diaphragms is currently a research hotspot. It can retain the high temperature resistance, high porosity and flexibility of the electrospun membrane, and integrate the characteristics of inorganic nanoparticles with it to improve the overall performance of the diaphragm.

[0057] 3) The nanofiber membrane of the present application has excellent electrolyte wettability and liquid retention rate. The carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, which makes the membrane have a very high liquid absorption rate, thereby enhancing the ionic conductivity of the membrane. In addition, the nanofiber core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the electrolyte wettability and liquid retention rate. At the same time, the uniform pore size and large specific surface area of ​​MOF also improve the electrolyte wettability.

[0058] 4) The nanofiber membrane of the present application has the ability to regulate lithium ion transport and induce uniform lithium deposition. The uniform pore size of MOF has the ability to regulate lithium ion transport and induce uniform lithium deposition, thereby inhibiting dendrite growth, reducing the overpotential during the charge and discharge cycle, and improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 These are photos of the electrolyte wettability experiment of the diaphragms in Examples 1-2 and Comparative Example 1.

[0060] Figure 2 It is a battery performance diagram of the separator in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0061] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0062] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0063] Example 1

[0064] The preparation of nanofiber membrane includes the following steps:

[0065] 1) Preparation of polyurethane nanofiber membrane: 2g polyurethane was dissolved in 8g organic solvent DMAC to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 18kV, an extrusion speed of 1.5ml / h, and a receiving distance of 15cm. The collected samples were hot-pressed at 100℃ and 8MPa for 3min to obtain a polyurethane nanofiber membrane with a fiber diameter of 400nm and a membrane thickness of 15µm.

[0066] 2) Preparation of metal chelated polyaniline layer: methanol was added dropwise to the pores of the polyurethane nanofiber membrane obtained in step (1) to pre-wet the pores, and then the membrane was placed in a 0.4 mol / L aniline hydrochloride and 0.5 mol / L ammonium persulfate solution at 2°C for 6 h, and then rinsed with 0.5 mol / L hydrochloric acid to remove residual precipitates, and then rinsed with water, and placed in 0.1 mol / L ammonia water for neutralization, and finally placed in a 0.6 mol / L zinc nitrate solution at 60°C to chelate metal zinc ions for 8 h, and dried at 70°C for 24 h to obtain a polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer;

[0067] 3) Preparation of ZIF-7 MOF layer: The polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer obtained in step (2) was vertically suspended in a ZIF-7 precursor solution, i.e., 75 ml of DMF solution containing 1.65 g of zinc nitrate and 0.88 g of benzimidazole, and reacted at 120°C for 8 h. The membrane was then rinsed and soaked with methanol and dried at 55°C for 24 h to finally obtain a polyurethane-based nanofiber membrane coaxially coated with a ZIF-7 layer. The size of the ZIF-7 particles was 50 nm.

[0068] Example 2

[0069] The preparation of nanofiber membrane includes the following steps:

[0070] 1) Preparation of polyurethane nanofiber membrane: 3g polyurethane was dissolved in 7g organic solvent DMF to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 30kV, an extrusion speed of 2ml / h, and a receiving distance of 25cm. The collected samples were hot-pressed at 120℃ and 15 MPa for 15min to obtain a polyurethane nanofiber membrane with a fiber diameter of 600nm and a membrane thickness of 45µm.

[0071] 2) Preparation of metal chelated polyaniline layer: methanol was added dropwise to the pores of the polyurethane nanofiber membrane obtained in step (1) to pre-wet the pores, and then the membrane was placed in a 0.5 mol / L aniline hydrochloride and 0.8 mol / L ammonium persulfate solution at 0°C for 8 h, and then rinsed with 1 mol / L hydrochloric acid to remove residual precipitates, and then rinsed with water, and placed in 0.3 mol / L ammonia water for neutralization, and finally placed in a 0.1 mol / L zinc nitrate solution at 90°C for chelating metal zinc ions for 4 h, and dried at 80°C for 8 h to obtain a polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer;

[0072] 3) Preparation of UIO-66-NH2MOF layer: The polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer obtained in step (2) was vertically suspended in a UIO-66-NH2 precursor solution, i.e., a solution of 7 ml formic acid and 20 ml ethanol containing 0.37 g zirconium chloride, and reacted at room temperature for 1 h. The membrane was then vertically suspended in a mixed solution of 20 ml ethanol, 7 ml methanol and 8 ml water containing 0.49 g 2-aminoterephthalic acid, and reacted at room temperature for 4 h. The membrane was then rinsed and soaked in methanol, and dried at 80°C for 8 h. Finally, a polyurethane-based nanofiber membrane coaxially coated with a UIO-66-NH2 layer was obtained. The size of the UIO-66-NH2 particles was 200 nm.

[0073] Example 3

[0074] The preparation of nanofiber membrane includes the following steps:

[0075] 1) Preparation of polyurethane nanofiber membrane: 0.5g polyurethane was dissolved in 9.5g organic solvent DMSO to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 15kV, an extrusion speed of 3ml / h, and a receiving distance of 8cm. The collected fibers were hot-pressed at 80℃ and 5MPa for 5min to obtain a polyurethane nanofiber membrane with a fiber diameter of 200nm and a membrane thickness of 20µm.

[0076] 2) Preparation of metal chelated polyaniline layer: methanol was added dropwise to the pores of the polyurethane nanofiber membrane obtained in step (1) to pre-wet the pores, and then the membrane was placed in a 0.1 mol / L aniline hydrochloride and 0.1 mol / L ammonium persulfate solution at 10°C for 1 h, and then rinsed with 0.1 mol / L hydrochloric acid to remove residual precipitates, and then rinsed with water, and placed in 0.05 mol / L ammonia water for neutralization, and finally placed in a 0.1 mol / L zinc nitrate solution at 70°C to chelate metal zinc ions for 6 h, and dried at 55°C for 10 h, to obtain a polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer;

[0077] 3) Preparation of UIO-66-NH2MOF layer: The polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer obtained in step (2) was vertically suspended in a UIO-66-NH2 precursor solution, i.e., a solution of 7 ml formic acid and 20 ml ethanol containing 0.12 g zirconium chloride, and reacted at room temperature for 1 h. The membrane was then vertically suspended in a mixed solution of 20 ml ethanol, 7 ml methanol and 8 ml water containing 0.29 g 2-aminoterephthalic acid, and reacted at room temperature for 1 h. The membrane was then rinsed and soaked in methanol, and dried at 60°C for 12 h. Finally, a polyurethane-based nanofiber membrane coaxially coated with a UIO-66-NH2 layer was obtained. The size of the UIO-66-NH2 particles was 20 nm.

[0078] Comparative Example 1

[0079] Comparative Example 1 is a ceramic coated diaphragm with a thickness of 12 μm.

[0080] Comparative Example 2

[0081] Comparative Example 2 is a PE-based film with a thickness of 12 μm.

[0082] Test Example 1

[0083] Performance Test 1: The diaphragms obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for thermal shrinkage and electrolyte wettability. The specific test methods are as follows. The test results are shown in Tables 1 and Figure 1 .

[0084] Thermal shrinkage rate: Cut the diaphragm into 100×100mm film samples, measure their longitudinal and transverse lengths, put them into a vacuum oven and bake them for 1h respectively, take out the diaphragm samples, cool them to room temperature, measure their longitudinal and transverse lengths again, calculate the thermal shrinkage rate, and characterize the heat resistance of the diaphragm. Test them at three temperatures of 105℃, 120℃ and 150℃ respectively.

[0085] Electrolyte Wettability: The electrolyte wettability uses electrolyte solvent (ethylene carbonate and dimethyl carbonate, with a mass ratio of 1:1) as the test object to observe the diffusion of the electrolyte at different times.

[0086] The separators in the examples and comparative examples were assembled into soft-pack batteries, and the rate curves were tested. The results are as follows: Figure 2 shown.

[0087] As shown in Table 1, the heat resistance of the diaphragms provided by Examples 1 to 3 and Comparative Example 1 is much higher than that of Comparative Example 2, indicating that the introduction of the composite functional layer significantly increases the thermal stability of the diaphragm. Figure 1 It can be seen that compared with Comparative Examples 1 and 2, the electrolyte wettability of the diaphragms provided by Examples 1 to 3 is significantly improved compared with the ceramic coated diaphragm provided by Comparative Example 1 and the commercial PE base film provided by Comparative Example 2, indicating that the spinning layer structure and composition can significantly improve the electrolyte wettability of the diaphragm. Figure 1 Analysis shows that the polyurethane-based nanofiber membrane coaxially coated with the MOF layer provided by the present invention has high electrolyte wettability and thermal stability of the diaphragm.

[0088] Depend on Figure 2 It can be seen that the ceramic coated diaphragm in Comparative Example 1 has no significant change in rate performance compared to the traditional PE-based membrane in Comparative Example 2. The rate performance of the nanofiber membrane in Examples 1 to 3 is significantly improved. This is because the carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, which makes the diaphragm have an extremely high liquid absorption rate. In addition, the nanofiber core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the wettability and liquid retention rate of the electrolyte. At the same time, the uniform pore size and large specific surface area of ​​MOF also improve the electrolyte wettability.

[0089] Table 1 Thermal shrinkage of the diaphragms in Examples 1-2 of the present invention and Comparative Example 1

[0090]

[0091] The above are only some of the embodiments of the invention, and do not constitute any formal limitation on the present application. All raw material ratios, upper and lower limits of working conditions and interval values ​​in the preparation process of the present application can realize the present application, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present application, can make some changes or modifications to the equivalent embodiments of the decoration by using the above technical content. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A polyurethane-based nanofiber membrane coaxially coated with a MOF layer, characterized in that: From the inside to the outside, it includes polyurethane nanofibers as a core layer, a metal chelate polyaniline layer as an intermediate layer, and MOF particles as a shell layer; The metal chelated polyaniline layer is modified on the surface of the polyurethane nanofiber core layer; The MOF particles and the metal chelated polyaniline layer are tightly combined; The polyurethane nanofibers as the core layer have a porous structure; The polyurethane-based nanofiber membrane coaxially coated with the MOF layer is prepared by the following steps: 1) Polyurethane nanofibers were obtained by electrospinning and polyurethane nanofiber membranes were obtained by hot pressing; 2) adding methanol to the polyurethane nanofiber membrane obtained in 1) for pre-wetting, then placing it in a solution containing aniline hydrochloride and ammonium persulfate, washing it with hydrochloric acid and water in sequence, then placing it in ammonia water for neutralization, then placing it in a zinc nitrate solution for chelation, and drying it to obtain a polyurethane nanofiber membrane with a surface modified metal chelated polyaniline layer; 3) The polyurethane nanofiber membrane with the surface modified metal chelated polyaniline layer obtained in 2) is vertically suspended in an organic solution containing a MOF precursor, reacted, rinsed and soaked with methanol, and dried to obtain the polyurethane-based nanofiber membrane coaxially coated with the MOF layer.

2. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: The diameter of the polyurethane nanofiber is 200-600 nm; The size of the MOF particles is 20-200 nm.

3. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: The polyurethane-based nanofiber membrane has a thickness of 10 to 100 μm.

4. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: The thickness of the polyurethane-based nanofiber membrane is 15-45 μm.

5. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: The MOF is selected from at least one of ZIF-7, ZIF-8, ZIF-67, ZIF-7-NH2, UIO-66-NH2, and HKUST-1.

6. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: 2) In In the solution containing aniline hydrochloride and ammonium persulfate, the concentration of aniline hydrochloride is 0.1~0.5mol / L, and the concentration of ammonium persulfate is 0.1~0.8mol / L; The treatment temperature is 0-10°C; The treatment time is 1 to 8 hours; The concentration of the zinc nitrate is 0.1-0.6 mol / L; The chelating temperature is 60-90°C; The chelation time is 4 to 8 hours; The hydrochloric acid concentration is 0.1~1 mol / L; The concentration of the ammonia water is 0.05-0.3 mol / L.

7. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: 2) In The drying temperature is 55-80°C; The drying time is 8 to 24 hours.

8. The polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to claim 1, characterized in that: 3) In The MOF precursor is selected from at least one of the precursors of ZIF-7, ZIF-8, ZIF-67, ZIF-7-NH2, UIO-66-NH2, and HKUST-1; The drying temperature is 55-80°C; The drying time is 8 to 24 hours.

9. An application of a polyurethane-based nanofiber membrane coaxially coated with a MOF layer according to any one of claims 1 to 8, characterized in that: For lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of nanofiber membrane with adsorption performance

    CN114855368A

  • Electrospinning-based aqueous zinc ion battery diaphragm and preparation method thereof

    CN118292277A